2021
DOI: 10.1093/schbul/sbaa181
|View full text |Cite
|
Sign up to set email alerts
|

Self-stigma in Serious Mental Illness: A Systematic Review of Frequency, Correlates, and Consequences

Abstract: Self-stigma is associated with poor clinical and functional outcomes in Serious Mental Illness (SMI). There has been no review of self-stigma frequency and correlates in different cultural and geographic areas and SMI. The objectives of the present study were: (1) to review the frequency, correlates, and consequences of self-stigma in individuals with SMI; (2) to compare self-stigma in different geographical areas and to review its potential association with cultural factors; (3) to evaluate the strengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
141
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(154 citation statements)
references
References 214 publications
11
141
2
Order By: Relevance
“…Experienced stigma, anticipated stigma, and self-stigma were identified as barriers to intimacy in ASD ( 33 ). This concurs with findings in serious mental illness where self-stigma has been associated with reduced capacity for intimacy and more negative parenting experiences ( 61 ). Self-stigma has been found to affect one in five people with ASD ( 7 , 62 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Experienced stigma, anticipated stigma, and self-stigma were identified as barriers to intimacy in ASD ( 33 ). This concurs with findings in serious mental illness where self-stigma has been associated with reduced capacity for intimacy and more negative parenting experiences ( 61 ). Self-stigma has been found to affect one in five people with ASD ( 7 , 62 ).…”
Section: Discussionsupporting
confidence: 91%
“…Future research should further investigate perceived stigma, experienced stigma, anticipated stigma, and self-stigma in gender-diverse autistic individuals. Self-stigma reduction [e.g., narrative enhancement and cognitive therapy ( 65 ) or peer-delivered interventions ( 61 )] might improve the clinical and functional outcomes in autistic women, although this remains to be investigated. A longitudinal examination is needed to investigate the potential relationships between camouflage strategies, stigma-related issues, capacity for intimacy, and parenting experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from the French national REHABase network showed that (i) most patients were dissatisfied with their interpersonal relationships at the time of admission and asked for interventions improving social function [36] and (ii) elevated self-stigma was frequent (31.2% of the 738 participants [37]) and was negatively associated with recovery-related outcomes. Self-stigma has been negatively associated with patient's longitudinal outcomes and to lower benefits from psychiatric rehabilitation [38]. Providing NECT to all participants aims at not excluding participants from interventions improving social function (e.g.…”
Section: Designmentioning
confidence: 99%
“…Many people with mental illness are not only aware of public prejudices, but turn them against themselves which is referred to as self-stigma (“I have a mental illness, therefore I must be lazy” [ 6 ]). Self-stigma is associated with a range of negative outcomes [ 7 ] and leads to impaired self-esteem and a sense of demoralization, the so-called why try effect (“Why should I even try to achieve my goals? I am not worthy or not able” [ 8 ]).…”
Section: Introductionmentioning
confidence: 99%